White matter plasticity in the adult brain - Sampaio-Baptista, C; Johansen-Berg, H (Elsevier, 2017)
The study of brain plasticity has tended to focus on the synapse, where well-described activity-dependent mechanisms are known to play a key role in learning and memory. However, it is becoming increasingly clear that plasticity occurs beyond the synapse. This review focuses on the emerging concept of white matter plasticity. For example, there is growing evidence, both from animal studies and from human neuroimaging, that activity-dependent regulation of myelin may play a role in learning. This previously overlooked phenomenon may provide a complementary but powerful route through which experience shapes the brain.